Bobby the brave (sometimes) - Yee, Lisa (Arthur A. Levine Books, 2010)
Fourth-grader Bobby is hurt when he hears his father, a former professional football player, say that the two of them are nothing alike, but finally summons the courage to talk about it after he suffers a public asthma attack.